AN OBJECTIVE EXPLICIT FORMULATION BASED ON THE OLDROYD-B CONSTITUTIVE EQUATION - Mompean, G.; Thompson, R. L.; Souza Mendes, P. R. (Revista de Engenharia Térmica, 2004)
In the present paper is shown how to obtain an objective explicit algebraic extra-stress model (AESM) based on differential constitutive equations for viscoelastic flows (Oldroyd B, White-Metzner, Phan-Thien-Tanner, etc). The formulation is developed for three-dimensional time-dependent flows. In a previous work, Mompean, 1998 obtained a non-objective algebraic model. This inconsistency is now removed introducing the relative-rate-ofrotation tensor making the model frame-invariant. A new generalized objective time derivative is also introduced, giving flexibility to the model. Calculations are performed with an Oldroyd B based AESM for a 4:1 contraction flow, showing good agreement with the original constitutive differential model. Several results with particular derivatives are obtained and an analysis guided by a flow type classifier is given. This formulation is able to include a prediction, not present in the Oldroyd B model, the viscometric second normal stress difference, N2.